Investigation of dyeing behavior of oxidative dye in fine structures of the human hair cuticle by nanoscale secondary ion mass spectrometry. Issue 3 (17th October 2014) - Kojima, T.; Yamada, H.; Saito, Y.; Nawa, T.; Isobe, M.; Yamamoto, T.; Aoki, D.; Matsushita, Y.; Fukushima, K.
<x xml:space="preserve">Abstract</x> Background/purpose In oxidative coloring, the hair cuticle layers are not only the penetration pathway for active ingredients but also one of the most important dyeing regions. The dyeing mechanism of oxidative dyes in fine structures of the cuticle remains unclear. To investigate the dyeing behavior of oxidative dyes in fine structures of the cuticle, hair cross‐sections were analyzed by nanoscale secondary ion mass spectrometry (NanoSIMS). Methods The preparation method of hair cross‐section for NanoSIMS measurement was improved. Improved hair cross‐sections were analyzed using NanoSIMS. Results The cuticle layer thickness of the hair cross‐section could be widened. It was confirmed that 12C− ions were more strongly detected from endocuticle than from other fine structures of cuticle. The NanoSIMS 12C− image and hue saturation intensity (HSI) D−/1H− ratio image of the hair, dyed with deuterium‐labeled oxidative dye, indicated that the endocuticle had a higher D−/1H− ratio than the other fine structures of the cuticle. It was substantiated that more colored chromophores were fixated in the endocuticle than in other fine structures of the cuticle. Conclusion The dyeing behavior of oxidative dyes in fine structures of hair cuticle was substantiated by NanoSIMS analysis using the improved hair cross‐section preparation method.